ASSESSMENT OF SPOT SATELLITE DATA FOR TROPICAL VEGETATION INVENTORY AND MONITORING IN SUMATRA - Yves Laumonier (SEAMEO BIOTROP, 1989)
Following a previous vegetation mapping in Sumatra island (Indonesia), an assessment of SPOT satellite capability to handle specific problems related to vegetation identification and monitoring from remote sensing data has been undertaken. Results of visual interpretation and multispectral analysis have shown the usefulness of SPOT data for the appraisal of tropical vegetation at medium scale. This was particularly striking for the swampy vegetation types including mangroves and for the secondary vegetation, for which significant improvements have been brought by multispectral classifications. A 20 m ground resolution is neither sufficient to provide information on primary forest patterns, nor to identify properly logged over areas. Never theless, several degrees of depletion of the forest and all the serial stages have been identified, which is a considerable progress compared with previous remote sensing means. SPOT is a very good alternative to medium scale aerial photographs for the production of medium scale (1 : 100 000 to 1 : 250 000) vegetation and land-use maps.